PENGARUH RISIKO NILAI TUKAR RUPIAH TERHADAP RETURN SAHAM : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - Desak Putu Suciwati; Mas’ud Machfoedz (Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
Rupiah exchange rate fluctuation occurred since July 1997 has risked rupiah depreciation on US Dollar and other mayor trading parther’s currencies, that are Yen (Jepang), Mark (Germany), Franc (French), Poundsterling (UK), Dollar (Singapore), and Dollar (Hongkong). The objective of this study is to examine the economic exposures differences of rupiah exchange rate before and after rupiah depreciation, and the different effect of rupiah exchange rate on stock return before and after rupiah depreciation.This study use Chow differential test to compare regression results at two different periods, period of 1994-1996 and 1998-2000 with the same sample. Two models regression equation were used and each model was differentially tested in two periods. Independent variable of the two models was average monthly rupiah real effective exchange rate (REER) during a year from December to November following year, and it was controlled by total debt (THUTANG) of the manufacture during a year. Dependent variable for the first regression model was EPS change of companies during a year, and for the second regression model was daily abnormal return accumulated during a year (CAR).Although regression analysis at the second period showed contrary or defferent result, but after tested with Chow test, it was indicated that economic exposure of rupiah exchange rate change on cash flow change at the second period was not different. It was proved, then, that the effects of rupiah exchange rate on stock return were different between period of before and after the rupiah depreciation.Keywords: Real Effective Exchange Rate, Exposure, Capital Adequacy, Earnings per share